1990
DOI: 10.1111/j.1439-0523.1990.tb00427.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inheritance of Resistance to Septoria Glume Blotch III. The Wild Wheat Species Aegilops Jongissima

Abstract: AhstractThe genetics of resistance to Septoria glume blotch (caused by the pathogen Septoria nodorum Berk.) in the wild wheat species Ae. longissima was investigated. The resistance was characterized by two parameters measured on detached leaves -lesion size (LS) and length of latent period (LP), and by disease severity (DS) under field conditions. Generations F,, F2 and F3, derived from a cross between two Ae. longissima accessions, were analyzed. The two parameters measured on detached leaves (LS and LP) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The reaction of F 1 plants and the segregation of F 2 and F 2:3 populations from the reciprocal crosses of 1644/1193 and 1193/1644 indicated that no maternal effects were involved in the inheritance of leaf rust and stem rust resistance (Tables 2 and 3). A similar result was reported by Ecker et al (2,3) in their study on the genetics of Septoria glume blotch resistance in the closely related species of A. speltoides and A. longissima. In contrast, marked differences were detected in the F 2 segregation ratio of reciprocal crosses between leaf rust resistant and susceptible A. speltoides accessions (E. Millet, unpublished data).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The reaction of F 1 plants and the segregation of F 2 and F 2:3 populations from the reciprocal crosses of 1644/1193 and 1193/1644 indicated that no maternal effects were involved in the inheritance of leaf rust and stem rust resistance (Tables 2 and 3). A similar result was reported by Ecker et al (2,3) in their study on the genetics of Septoria glume blotch resistance in the closely related species of A. speltoides and A. longissima. In contrast, marked differences were detected in the F 2 segregation ratio of reciprocal crosses between leaf rust resistant and susceptible A. speltoides accessions (E. Millet, unpublished data).…”
Section: Resultssupporting
confidence: 82%
“…This study was the first to characterize the genetics of disease resistance in A. sharonensis, and one of the few completed in any of the species of the section Sitopsis (2,3). Our results clearly demonstrated that resistance to wheat leaf rust, stem rust, and powdery mildew in A. sharonensis is controlled by dominant genes with major effect.…”
Section: Resultsmentioning
confidence: 51%
“…This is the first report that genes in A. longissima confer eyespot resistance. Although A. longissima was not previously known to he resistant to eyespot, it was reported to be resistant to Septoria glume blotch, powdery mildew, and rust diseases (2,8,18). Thus, A. longissima is a potential source of resistance to eyespot as well as these other diseases for wheat improvement programs.…”
Section: Discussionmentioning
confidence: 91%
“…(2n = 14, S'S') is a diploid species in the section Sitopsis of Aegilops (50) that has been used as a donor of numerous genes for wheat improvement, including disease resistance (21). Ecker et al (18) identified A. longissima accessions that were highly resistant to Septoria glume blotch of wheat. Powdery mildew resistance gene Pml3 was mapped to the short arm of chromosome 3S' of A. longissima and transferred into 'Chinese Spring' wheat (7,8).…”
mentioning
confidence: 99%
“…Resistance in Ae. longissima to Septoria glume blotch, powdery mildew, and rusts of wheat has been reported (Ecker et al 1990;Cenci et al 2003;Anikster et al 2005). Ae.…”
Section: Introductionmentioning
confidence: 99%